The Effect of Adding Activated Sludge and Types of Series Circuit Systems Microbial Fuel Cell (MFC) Using Chinese Food Restaurant Wastewater - Danang Jaya; Tunjung Wahyu Widayati; Singgih Adi Nugroho; Firda Ellysa (Eksergi, 2022)
Electricity consumption expands every year. However, in Indonesia, electricity is still highly dependent on conventional energy sources such as coal. A microbial fuel cell (MFC) is one of the alternative inventions that consists of a series of tools which converts chemical energy into electrical energy in the presence of microbial metabolism. In addition to produce electrical energy, it may also help to solve environmental issues by dealing with waste. This research was purposed to investigate the potency of Chinese food restaurant waste as substrate to generate electricity in microbial fuel cell. The research was done in three stages: wastewater preparation, assembly of MFC tools in various circuits, and running MFC processes. Results showed that the best electrical average (1.02 V) was found in the treatment system without active sludge. The best circuit was in the system in 4 series, which obtained a maximum voltage of 3.76 V and the largest power density of 62.66  mW/m2. In addition, with the addition of active sludge, biological oxygen demand (BOD) of the wastewater could be lowered up to 29.27%, and chemical oxygen demand (COD) up to 51.58%. Total suspended solid (TSS) could be decreased up to 49% on the sample withoud sludge addition.